Hijacking of immune defences by biofilms: a multifront strategy. Issue 10 (26th November 2019) - Campoccia, Davide; Mirzaei, Rasoul; Montanaro, Lucio; Arciola, Carla Renata
Abstract: Biofilm formation by pathogens and opportunistic bacteria is the basis of persistent or recurrent infections. Up to 80% of bacterial infections in humans are associated with biofilms. Despite the efficiency of the evolved and complex human defence system against planktonic bacteria, biofilms are capable of subverting host defences. The immune system is not completely effective in opposing bacteria and preventing infection. Increasing attention is being focussed on the mechanisms enabling bacterial biofilms to skew the coordinate action of humoral and cell mediated responses. Knowledge of the interactions between biofilm bacteria and the immune system is critical to effectively address biofilm infections, which have multiplied over the years with the spread of biomaterials in medicine. In this article, the latest information on the interactions between bacterial biofilms and immune cells is examined and the areas where of information is still lacking are explored.